FRI0764-HPR Mortality in patients with rheumatoid arthritis and end stage renal disease. (15th June 2017) - Paudyal, S; Waller, J; Oliver, A; Le, B; Zleik, N; Nahman, NS; Carbone, L
Abstract : Background: Cardiovascular related mortality is higher in patients with rheumatoid arthritis (RA) compared to the general population, and accounts for more than half of all deaths in end stage renal disease (ESRD). The prevalence of ESRD is increasing and there are an increasing number of older patients with RA. Our recent study demonstrated approximately 1% of patients with ESRD have RA. The implications of ESRD on RA relative to the burdens of cardiovascular diseases, cardiovascular and all-cause mortality are not known. Objectives: To determine whether patients with RA who have ESRD are at increased risk for cardiovascular disease (CVD) events, cardiovascular mortality and all-cause mortality compared to the general population of patients with ESRD. Methods: Retrospective cohort study of adult patients (age 18 and older) with ESRD receiving renal replacement therapy (hemodialysis or peritoneal dialysis) in the United States Renal Data System (USRDS) who initiated dialysis between 2005 and 2008 followed for up to five years. Patients with an ICD-9 diagnostic code for RA on or before the start of dialysis and a 5% random sample of those without RA were included. Incident cardiovascular events, cardiovascular related mortality and all-cause mortality was determined in those with RA compared to those without RA. Results: There were 2, 824 subjects including 407 with RA and 2, 417 without RA included in the analyses. There was no significant difference in the total number of incident CVD events by RA status (n=311 (76.4% RA) vs. n=1936 (80.1% without RA) (p=0.09). 76 patients with RA (18.7%) died from a CVD related cause compared to 403 without RA (16.7%), (p=0.32). Overall mortality was significantly higher in those with RA (n=226 (55.5%) vs. n=970 (40.1%) (p<0.01). Compared to those without RA, those with RA had a significantly shorter mean time in months from start of dialysis to any incident CVD event (17.5 (12.4)) vs. 21.2 (14.1) (p<0.01), CVD death, (34.2 (12.5) vs.37.9 (12.6) p=0.02), or all-cause mortality (33.1 (13.0) vs. 37.8 (12.6) (p<0.01). In final adjusted models, RA was associated with an increased risk for both CVD related mortality (aHR=1.23 (95% CI 1.05–1.43)) and all-cause mortality (aHR=1.22 (1.05 – 1.42) within five years. Risk factors for CVD and overall mortality included older age, a higher Charlson comorbidity index, tobacco use, needing assistance with ADLs and living in a nursing home. Black race and Hispanic ethnicity was associated with significantly less CVD and all cause-related mortality. Conclusions: Physicians treating patients with RA and ESRD should be aware that these patients are at increased risk for cardiovascular related mortality and all-cause mortality compared with the general population of ESRD patients. Patients with ESRD and RA at higher risk for mortality can be identified by both demographic risk factors as well as overall health status. Acknowledgements: Funding for this work was supported by the Translational Research Program (TRP) at the Medical College of Georgia and the Medical and Graduate Student Preceptorship award from the Rheumatology Research Foundation, Atlanta, Georgia. Disclosure of Interest: None declared